2015
DOI: 10.1590/s0100-204x2015000500003
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Garlic common latent virus in Argentina, and phylogenetic and recombination analyses of isolates

Abstract: -The objective of this work was to estimate the incidence and prevalence of Garlic common latent virus (GarCLV) in the main production regions of garlic (Allium sativum) in Argentina, and to perform phylogenetic and recombination analyses in isolates from these regions. Leaf samples (3,050) were taken from four garlic commercial types, in 13 departments of the four main garlic-producing provinces of Argentina, in a 1,175-ha sampling area. Virus infection was evaluated with DAS-Elisa test using specific antiser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(57 reference statements)
0
7
0
Order By: Relevance
“…The gain in productivity through the use of virusfree clones has been widely reported in researches (Silva et al, 2010;Melo et al, 2011;Bereda & Paduch-Cichal, 2016) and marketable plantations. According to Resende et al (2000), the virus-free clone shows a vegetative vigor superior to virus-infected ones, which leads to an increased productivity.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The gain in productivity through the use of virusfree clones has been widely reported in researches (Silva et al, 2010;Melo et al, 2011;Bereda & Paduch-Cichal, 2016) and marketable plantations. According to Resende et al (2000), the virus-free clone shows a vegetative vigor superior to virus-infected ones, which leads to an increased productivity.…”
Section: Resultsmentioning
confidence: 97%
“…Productivity reduction varies according to the levels of viral infection of the cultivar, genetic material, and years of conventional clove multiplication. In this sense, Silva et al (2010) observed a higher productivity in cloves from tissue culture for nine consecutive years, in comparison to the conventional multiplication. Depending on the cultivar used, the production tends to reduce from the third or fourth year of successive cultivation.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…ORF5 contains a coat protein (CP) encoding sequence (Yadav & Majumder 2019). Earlier phylogenetic analyses on the complete nucleotide (nt) sequence of the CP region showed that most GarCLV isolates were divided into two major groups only, which had relatively low diversities between them (Parrano et al 2012;Pramesh & Baranwal 2013;Torrico et al 2015). However, the presence of a third phylogroup that was predicted by Parrano et al (2012) has been proven recently by Santosa and Ertunc (2020).…”
mentioning
confidence: 99%